Inconsistencies in mapping current distribution in transcranial direct current stimulation - Jwa, Anita S.; Goodman, Jonathan S.; Glover, Gary H. (Frontiers in Neuroimaging, 2023)
Transcranial direct current stimulation(tDCS) is a non-invasive neuromodulation technique that has been widely studied both as a therapy for neuropsychiatric diseases and for cognitive enhancement. However, recent meta-analyses have reported significant inconsistencies amongst tDCS studies. Enhancing empirical understanding of current flow in the brain may help elucidate some of these inconsistencies. In this study, we investigated tDCS-induced current distribution by injecting a low frequency current waveform in a phantom and in vivo. MR phase images were collected during the stimulation and a time-series analysis was used to reconstruct the magnetic field. A current distribution map was derived from the field map using Ampere’s law. The current distribution map in the phantom showed a clear path of current flow between the two electrodes, with more than 75% of the injected current accounted for. However, in brain, the results did evidence a current path between the two target electrodes but only some portion (~25%) of injected current reached the cortex demonstrating that a significant fraction of the current is bypassing the brain and traveling from one electrode to the other external to the brain, probably due to conductivity differences in brain tissue types. Substantial inter-subject and intra-subject (across consecutive scans) variability in current distribution maps were also observed in human but not phantom scans. This finding may help explain some of the inconsistencies reported in other studies.